Vascular silicone injection of fresh cadaveric cow cranium: Alternative training model for the human brain [Taze İnek kranium kadavrasının vasküler silikon İnjeksiyonu: eğitim modeli olarak İnsan beynine bir alternatif] - (:unkn) unknown (Ege University Press, 2015)
Background: Anatomical and physiological variations of the human brain's vascular system can be observed via silicone injection of the arterial and venous systems. As a novel method, the injection of a fresh cadaveric cow cranium with silicone is an alternative to using the human brain for microanatomical studies. Objective: To report on an improved method for the colored silicone injection of a fresh cadaveric cow cranium using a silicone injection technique. Methods: Five fresh cow crania were injected as an alternative to human brains for microanatomical dissection, in which the preparation consisted of the irrigation of the major vessels and the injection of colored silicone. Cannulation of the internal carotid arteries and the internal jugular veins with catheters was performed, and the vasculature was irrigated with water (major arteries and veins). The fixation of the specimen with either formaldehyde or alcohol, and the colored injection of the arteries and veins with red and blue silicone, respectively, was then performed. Results: The silicone injections resulted in the deeper penetration of the colored solutions into the small cerebral vessels and mesenchymal structures of the fresh cadaveric cow crania. Of the five injected specimens, four exhibited successful injections, while one had suboptimal results. Conclusion: Silicone injection of the cadaveric cow brain, based on the anatomical and physiological assessment of the vasculature of the specimen for microanatomical studies, is suggested as an alternative to using human brain specimens. © 2015, Ege University Press. All rights reserved.
Keywords: Cadaver; Cow cranium; Dissection; Microneurosurgical training; Resident training; Silicone injection